2013
DOI: 10.1158/0008-5472.can-12-3542
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Alters Monocyte Differentiation to Favor Generation of Cancer-Supporting M2 Macrophages in the Tumor Microenvironment

Abstract: Current therapy of gynecologic malignancies consists of platinum-containing chemotherapy. Resistance to therapy is associated with increased levels of interleukin (IL)-6 and prostaglandin E2 (PGE 2 ), 2 inflammatory mediators known to skew differentiation of monocytes to tumor-promoting M2 macrophages. We investigated the impact of cisplatin and carboplatin on 10 different cervical and ovarian cancer cell lines as well as on the ability of the tumor cells to affect the differentiation and function of coculture… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
217
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(227 citation statements)
references
References 52 publications
8
217
1
1
Order By: Relevance
“…The phenotype and composition of dispersed tumors (and expanded TILs) were analyzed by flow (9,(12)(13)(14)(15) and time-offlight mass cytometry (CyTOF; ref. 16; Supplementary Methods).…”
Section: Tils and Tumor Cell Analysesmentioning
confidence: 99%
“…The phenotype and composition of dispersed tumors (and expanded TILs) were analyzed by flow (9,(12)(13)(14)(15) and time-offlight mass cytometry (CyTOF; ref. 16; Supplementary Methods).…”
Section: Tils and Tumor Cell Analysesmentioning
confidence: 99%
“…Dijkgraaf et al showed that blocking NF-B signaling stopped platinum chemotherapy's effect of increased IL-6 and PGE2 causing more M2 differentiation. Thus anti-IL-6 therapy is another recom-mended route for therapies (Dijkgraaf et al, 2013). Other approaches include inhibition of GM-CSF in vivo and decreased VEGF and CCL-5 as ways to reduce monocyte recruitment (Bayne et al, 2012;Elbarghati et al, 2008;Pylayeva-Gupta et al, 2012).…”
Section: Possible Treatment Strategies Using Various Proteins and Smamentioning
confidence: 99%
“…The exact mechanism behind this hematologic paraneoplastic manifestation is unclear but is most likely caused by tumor-produced hematopoietic cytokines ( e.g. GM-CSF, G-CSF, IL-6, PGE2) 13 , 29 that are known to mobilize and expand MDSC and macrophages from the bone marrow. 30 In line with our previous studies in lung and cervical cancer, 26 , 31 these myeloid cells are suppressive since in vitro depletion unleashed T cell reactivity to recall antigens and tumor antigens.…”
Section: Discussionmentioning
confidence: 99%